Correlation of the effect of beta-lactamase inhibitors on the beta-lactamase in growing cultures of gram-negative bacteria with their effect on the isolated beta-lactamase. - Easton, C J (1984)
The effectiveness of clavulanic acid, sulbactam, quinacillin sulfone, and the carbapenems MM13902 and MM4550 as inhibitors of TEM-2 beta-lactamase in growing cultures of gram-negative bacteria has been studied. Each of these beta-lactams inhibited the enzyme in intact cells, and the nature of the inhibition correlated with studies on the purified enzyme. The potency of these compounds as inhibitors of the beta-lactamase in vivo can be correlated with the amounts hydrolyzed by the purified enzyme under saturating conditions during the inhibition of the enzyme in vitro.